Lea Castle Queen's County - Wynne, Luttrell, c. 1739-1814 (1790)
Ruins of the 13th century Lea Castle, near Portarlington, County Laois, Ireland.
Damage done to right part of drawing but conserved.
Engraved as Plate 71 in Volume 1 of "Antiquities of Ireland" by Francis Grose and published by Samuel Hooper, High Holborn, London, 1794.
Inscribed in ink on verso of drawing and crossed out: Reduced.
Inscribed in ink on verso of drawing: Not done.
Inscribed in pencil u.r.: South Coast.
Title inscribed in ink u.l..
Keywords: Lea Castle (Laois, Ireland) -- 1790-1800.; Castles & palaces -- Ireland -- Laois (County) -- 1790-1800; Ruins -- Ireland -- Laois (County) -- 1790-1800; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.